SAT0244 A Phase Iib Study of the Efficacy and Safety of Subcutaneous Clazakizumab (ANTI-IL-6 Monoclonal Antibody) with or without Methotrexate in Adults with Moderate-To-Severe Active Rheumatoid Arthritis and an Inadequate Response to Methotrexate. (10th June 2014) - Weinblatt, M.; Mease, P.; Mysler, E.; Takeuchi, T.; Drescher, E.; Berman, A.; Zilberstein, M.; Xing, J.; Emery, P.
Abstract : Background: Clazakizumab (CLZ) is a humanized anti-interleukin-6 (IL-6) monoclonal antibody that potently neutralizes IL-6 signalling. Objectives: This study evaluated the safety and efficacy of subcutaneous CLZ with or without MTX versus placebo (pbo) or adalimumab (ADA). Methods: Patients with moderate-to-severe RA and an inadequate response to MTX were randomized equally to receive pbo + MTX; 25, 100 or 200 mg CLZ + MTX; 100 or 200 mg CLZ without MTX; and ADA 40 mg every other week + MTX for 24 weeks. The primary endpoint was ACR 20 response rate at Week 12. Key secondary endpoints at Week 24 were ACR 20, ACR 50 and ACR 70 response rates, Health Assessment Questionnaire-Disability Index (HAQ-DI) improvements and remission defined as Disease Activity Score (DAS)28 (C-reactive protein, CRP) <2.6, Clinical Disease Activity Index (CDAI) <2.8 and Simplified Disease Activity Index (SDAI) <3.3. Results: A total of 418 patients were randomized and received treatment. Baseline characteristics were balanced across the arms; 82% female, mean age 50 years, mean duration of RA 5.9 years, mean DAS28 (CRP) 5.94, and 80% rheumatoid factor positive. The primary endpoint was met; ACR 20 response rates were statistically significantly higher in all CLZ arms versus pbo + MTX. All CLZ treatment groups were associated with improved ACR 20/50/70 response rates, HAQ-DI and remission versus pbo + MTX through Week 24. Rates of remission per DAS28 (CRP) <2.6, SDAI <3.3 and CDAI <2.8 were numerically higher in the CLZ + MTX arms compared with ADA + MTX. Treatment with CLZ in combination with MTX resulted in higher response rates than monotherapy. However, no clear dose response for efficacy was noted. The rates of serious adverse events ranged from 8.3 to 13.3% in CLZ arms versus 3.3% for pbo + MTX and 5.1% for ADA + MTX. Rates of serious infections were similar as reported for all CLZ arms and ADA versus none in pbo. CLZ was associated with mostly mild injection-site reactions, few of which led to discontinuation. As expected based on its mode of action, CLZ treatment was associated with increased transaminases (mainly in combination with MTX), increased lipids and haemoglobin, and decreased polymorphonuclear neutrophils and platelets. Conclusions: Clazakizumab as monotherapy or in combination with MTX demonstrated efficacy in controlling the signs and symptoms of RA. At Week 24, remission rates with clazakizumab + MTX trended higher than with ADA + MTX. Its safety profile was consistent with the known pharmacology of IL-6 blockade. Clazakizumab is a promising future treatment for RA that warrants further investigation. Disclosure of Interest: M. Weinblatt Grant/research support: BMS, Crescendo Bioscience, UCB, Consultant for: AbbVie, BMS, Crescendo Bioscience, Janssen, Roche, UCB, P. Mease Grant/research support: AbbVie, Amgen, Biogen Idec, BMS, Celgene, Eli Lilly, Genentech, Janssen, Novartis, Pfizer, Roche, UCB, Vertex, Consultant for: AbbVie, Alder Pharmaceuticals, Amgen, Biogen Idec, BMS, Celgene, Cypress Biosciences, Eli Lilly, Genentech, Janssen, Novartis, Pfizer, Roche, UCB, Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB, E. Mysler Grant/research support: BMS, Consultant for: BMS, Speakers bureau: BMS, T. Takeuchi Speakers bureau: Abbott, Astellas Pharma, BMS, Chugai Pharma, Eisai Pharma, Mitsubishi-Tanabe Pharma, Pfizer, Takeda Pharaceutical, E. Drescher: None declared, A. Berman: None declared, M. Zilberstein Employee of: BMS, J. Xing Shareholder of: BMS, Employee of: BMS, P. Emery Grant/research support: AbbVie, BMS, Merck, Pfizer, Roche, Consultant for: AbbVie, BMS, Merck, Pfizer, Roche, Takeda DOI: 10.1136/annrheumdis-2014-eular.3754